Clinical profile on incidence and course of Retinopathy of Prematurity in a tertiary care hospital of Northern India - Grang, Parveen; Kaur, Prempal; Singh, Karamjit; Sareen, Ashwani; Singh, Bhavkaran (Asian Journal of Medical Sciences, 2021)
Background: Retinopathy of prematurity (ROP) is a vaso-proliferative disorder of retina of preterm infants. It remains the leading cause of childhood blindness worldwide. Aggressive posterior retinopathy of prematurity (APROP) is rapidly progressive severe form of ROP. Aims and Objectives: The present study was done to assess incidence and evaluate course of ROP in preterm babies born before 34 weeks and birth weight <1750 grams. Material and Methods: The current study was a two year prospective observational study. Screening of all neonates born with gestational age ≤34 weeks and birth weight <1750 grams was done for ROP at 4 weeks of their postnatal age by indirect ophthalmoscopy and followed up till vascularization was complete. All neonates identified with APROP and ROP with plus disease was treated with double-frequency Nd YAG laser. Results: Of 318 neonates screened, 34.9% neonates (111) were observed to have ROP. 2.5% (8/318) neonates diagnosed with APROP and 4.4% neonates (14/318) having ROP with plus disease including pre-threshold and threshold ROP were treated with double frequency Nd Yag laser. All 14 treatment requiring ROP babies and 6 APROP babies showed total regression while one neonate with APROP succumbed to septicaemia during follow up and one APROP baby had to be referred to higher centre after he developed partial retinal detachment (RD) (Stage 4a). Conclusion: 34.9% had ROP, only 6.28% needed intervention. Laser monotherapy even when administered early has lesser favorable structural and functional outcome in APROP as compared to classical ROP.